Mulheres apenadas: avaliação de subtipos de psicopatia e associações com empatia e assertividade - Santos, Bruna Staevie dos (Universidade do Vale do Rio dos Sinos, 2018)
Psychopathy makes up interdependent symptomatic axes (affective distancing and antisocial lifestyle). The primary subtype is the one that includes the most symptoms related to affective distancing and the secondary subtype presents mostly symptoms of antisocial lifestyle. Cognitive (EC) and affective (AS) empathy, drug involvement, and assertiveness levels differ among subtypes. Thus, this research aimed to investigate the relationship between empathy, assertiveness and drug use in primary and secondary psychopathic women in jail. It is a quantitative, cross-sectional, comparative and explanatory research, composed of 61 women from state prisons, who underwent individual interviews and application of the instruments Hare Scale, Multidimensional Interpersonal Reactivity Scale, Assertive Skills Inventory for Women, Use Screening Questionnaire of alcohol, tobacco and other substances and sociodemographic / criminal questionnaire. The research was approved by the UNISINOS Ethics Committee under opinion No. 2,685,214 as well as by the SUSEPE Research Analysis Group. Through multiple regression analysis the results showed that AE plus drug use were influencing factors for secondary psychopathy. In addition, empathy, AS, drug and alcohol use, and assertiveness were significant in the mean difference between psychopaths and nonpsychopaths in the women in the sample.
Keywords: Psicopatia; Mulheres; Assertividade; Empatia; Drogas; Psychopathy; Women; Assertiveness; Empathy; Drugs; ACCNPQ::Ciências Humanas::Psicologia